2018
DOI: 10.1111/cas.13534
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of an in vivo simulating co‐culture assay platform for genotoxicity of multi‐walled carbon nanotubes

Abstract: Engineered nanomaterials (ENM) are now used in a wide variety of fields, and, thus, their safety should urgently be assessed and secured. It has been suggested that inflammatory responses via the phagocytosis of ENM by macrophages is a key mechanism for their genotoxicity. The present study was conducted to establish a mechanism‐based assay to evaluate the genotoxicity of ENM under conditions simulating an in vivo situation, featuring a co‐culture system of murine lung resident cells (GDL1) and immune cells (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 44 publications
(73 reference statements)
0
21
0
Order By: Relevance
“…The authors reported a stronger mutation frequency in co-cultured GDL1 cells and RAW 264.7 macrophages over monocultured GDL1 cells noting a greater IL-1α and IL-1β production when macrophages were present. The authors also reported the presence of the free-radical-induced DNA lesion, 8-hydroxydeoxyguanosine (8-OHdG), in co-cultured GLD1 cells was greater than monocultured cells indicative of secondary mechanisms [ 11 ]. In the recent work of Evans and colleagues investigating SPION toxicity in co-cultures of 16HBE14o − and d.THP-1 macrophages, the authors reported secondary genotoxicity at concentrations of 10, 50 and 100 µg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported a stronger mutation frequency in co-cultured GDL1 cells and RAW 264.7 macrophages over monocultured GDL1 cells noting a greater IL-1α and IL-1β production when macrophages were present. The authors also reported the presence of the free-radical-induced DNA lesion, 8-hydroxydeoxyguanosine (8-OHdG), in co-cultured GLD1 cells was greater than monocultured cells indicative of secondary mechanisms [ 11 ]. In the recent work of Evans and colleagues investigating SPION toxicity in co-cultures of 16HBE14o − and d.THP-1 macrophages, the authors reported secondary genotoxicity at concentrations of 10, 50 and 100 µg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported a stronger mutation frequency in co-cultured GDL1 cells and RAW 264.7 macrophages over monocultured GDL1 cells noting a greater IL-1α and IL-1β production when macrophages were present. The authors also reported the presence of the free-radical-induced DNA lesion, 8-hydroxydeoxyguanosine (8-OHdG), in cocultured GLD1 cells was greater than monocultured cells indicative of secondary mechanisms (Fukai et al, 2018). In the recent work of Evans and colleagues investigating SPION toxicity in co-cultures of 16HBE14o − and d.THP-1 macrophages, the authors reported secondary genotoxicity at concentrations of 10, 50 and 100 µg/ml.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, enhanced cytokines IL-10, and TGF-β, restricted tumor metastasis. 36 , 41 Indeed, the role of tumor destruction of CNTs did not rule out. Another study on breast cancer was performed with CNTs, which confirmed that CNTs could reduce tumor size.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of MWCNTs in vivo resulted in cytokines production such as TNF‐α and IL‐1β from immune cells which involved in creating the toxicity. 36 In a 90-day study by the intravenous injection of MWCNT, no changes in mice weight were observed, while the toxic effects were observed, and also the mice survive, despite the toxicity. 37 In another study on Sprague–Dawley rats with injected intratracheally of 0.5, 2, and 5 mg MWCNTs, TNF-α discharge was increased from macrophages.…”
Section: The Pulmonary Toxicity Assessment Of Carbon Nanotubesmentioning
confidence: 98%